bahasa inggris - Safitri; Fifi Yasmi; Vivina Eprillison (Global Action and Education for Society, 2026)
This study aims to determine 1) the effect of learning discipline on learning achievement, 2) the effect of learning discipline through learning motivation as an intervening variable on learning achievement, 3) the effect of learning interest on learning achievement, 4) the effect of learning interest through learning motivation as an intervening variable on learning achievement, 5) the influence of peers on learning achievement, 6) the influence of peers through learning motivation as an intervening variable on learning achievement, 7) the effect of parental support on learning achievement, 8) the effect of parental support through learning motivation as an intervening variable on learning achievement, and 9) the effect of learning motivation on learning achievement.This study is a descriptive study. The population was 137 eighth-grade students at SMP Negeri 1 Sungai Beremas. Sampling was conducted using proportional random sampling. The instrument used for the study was a closed-ended questionnaire with path analysis and hypothesis testing using t-tests and multilevel tests.The results of the study showed that 1) there was an influence of learning discipline on learning motivation with a path coefficient value of 0.466 and a t-count value of 3.397> t-table 1.977, 2) there was no influence of learning interest on learning motivation with a path coefficient value of 0.049 and a t-count value of 0.320<t-table 1.977, 3) there was no influence of peers on learning motivation with a path coefficient value of 0.082 and a t-count value of 1.007<t-table 1.977, and 4) there was an influence of parental support on learning motivation with a path coefficient value of 0.285 and a t-count value of 2.869>t-table 1.977. 5) There is an effect of learning discipline on learning achievement with a path coefficient value of 0.284 and a calculated t value of 2.376 > t table 1.977, 6) There is an effect of learning interest on learning achievement with a path coefficient value of 0.407 and a calculated t value of 3.220 > t table 1.977, 7) There is an influence of peers on learning achievement with a path coefficient value of 0.410 and a calculated t value of 6.029 > t table 1.977, 8) There is an effect of parental support on learning achievement with a path coefficient value of 0.268 and a calculated t value of 3.146 > t table 1.977, 9) There is an effect of learning motivation on learning achievement with a path coefficient value of 0.148 and a calculated t value of 2.034 > t table 1.997.Learning discipline, students should better organize their study schedule at home so they know when to play and study. Interest in learning, students should be more focused in learning so as not to get bad grades. As a solution, teachers should provide time for ice breaking so that students can refocus. Peers, teachers should pay more attention to their students so that students do not feel left out from their friends. Parental support, parents should be able to pay more attention to their children so that students do not feel a lack of attention, both from others around them and from their parents. Learning motivation, students should do their assignments regularly and try to get satisfactory grades by working together with their friends at home.